Clinicians' perspectives of parental decision-making following diagnosis of a severe congenital anomaly: a qualitative study. Issue 5 (6th June 2017) - Lotto, Robyn; Smith, Lucy K; Armstrong, Natalie
Abstract : Objective: To explore clinicians' perspectives on supporting parents' decision-making following diagnosis of a severe congenital anomaly, and how this is shaped by current policy. Methods: This paper reports data collated as part of a larger project examining parents' decision-making following antenatal diagnosis. The focus of this paper is the data arising from semistructured interviews conducted with 18 clinicians, with findings further supported by data generated from consultations between clinicians and parents. All interviews and consultations were audio-recorded and transcribed verbatim, with analysis based on the constant comparative approach. Results: Three key themes emerged which together shape the practice of clinicians working in this area: first, the law governing termination of pregnancy (TOP) and how clinicians believe this influences the context in which decisions about whether to terminate or continue an affected pregnancy are made; second, approaches to the management of cases seen as particularly challenging; and third, how clinicians understand their role when working with parents. These themes combine to create a strong desire on the part of clinicians for parents to engage in a particular 'rational' form of decision-making and to be able to demonstrate the enactment of this. This is seen as important in order to ensure the 'right' decision has been reached and, particularly when the decision is to terminate, will withstand possible scrutiny. Conclusions: The policy context in which these decisions are made strongly shapes how clinicians practise and what they want to see from the parents with whom they work. The ways in which they seek to overcome the difficulties in interpreting the law may result in variations in the offer of late TOP, both between and within units. This may inadvertently affect the options available to women least able to engage in this idealised form of decision-making.